A Systematic Review and Bibliometric Analysis of the Scientific Literature on the Early Phase of COVID-19 in Italy - Federica Turatto; Elena Mazzalai; Federica Pagano; Giuseppe Migliara; Paolo Villari; Corrado De Vito (Frontiers Media S.A., 2021)
Background: Studying the scientific literature about COVID-19 and Italy, one of the first countries to be hit by the pandemic, allows an investigation into how knowledge develops during a public health emergency.Methods: A systematic review of the literature was conducted to identify articles published on the topic between January and April 2020. Articles were classified according to type of study. Co-occurrence of terms, and geographic and temporal trends were analyzed.Results: Of the 238 articles included in the systematic review, the majority (37%) focused on hospital and clinical management of COVID-19, while 23.9% were commentaries. Epidemiological studies constituted 45.5% of the articles published by authors with non-Italian affiliations.Conclusion: The scientific articles on COVID-19 in Italy were varied in type of study, though with limited international impact. The lockdown and the pressure placed on hospitals during the first wave of the pandemic mainly resulted in publications on disease management and commentaries.